The Numbers Killer - Jenifer Ruff (Middletown, DE Greyt Companion Press, 2019)
"Agent Victoria Heslin is tasked with tracking down the murderer in what first appears to be a mafia-style hit to silence a witness, but the facts on the ground say otherwise. As Victoria pursues her meager leads, the calls start coming in--more bodies, each with similar markings: 'cheater' and 'you'll be sorry' but the corpses have little else in common. Then the killer leaves a personal note for Victoria. And another. Victoria must find the deranged spree killer before the body count rises by determining what deep, dark secrets are motivating the murders. Until a common denominator is discovered between the victims, anyone might be next--including Victoria."
Keywords: Federal Bureau of Investigations; Murder Investigations; Secrecy; Serial murderers